Anteecology and seed biology of false chestnut (Aesculus hippocastanum L) - Choriyev Bakhodir Mamarajabovich (Genius Publishing Group, 2023)
This article provides information on the antecology and seed biology of the false chestnut (Aesculus hippocastanum L), the formation of seeds enclosed in a longitudinal fruit capsule, and its biological structure and benefits for human life.
Keywords: False chestnut; Seed; big tree; series